FAKTOR-FAKTOR PENYEBAB PROKRASTINASI AKADEMIK PADA SISWA SMA SERTA IMPLIKASINYA DALAM LAYANAN BIMBINGAN DAN KONSELING - Selma, Selma Karmila Dewi; Neviyarni, Neviyarni (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Academic procrastination refers to the tendency to delay academic tasks or obligations until just before the deadline. This behavior negatively affects performance, causes stress, guilt, and decreases self-confidence among students. The objective of this study is to identify the factors that contribute to academic procrastination in high school students and explore its implications for guidance and counseling services. A descriptive quantitative approach was used, involving the population of students in grades X E and XI F at SMAN 2 VII Koto Sungai Sarik during the 2024/2025 academic year, totaling 102 students. A total sampling technique was applied, allowing the study to include all members of the population for more representative and accurate data. The research instrument used a Likert scale model to assess factors contributing to academic procrastination. The findings revealed that high-category internal factors included anxiety, difficulty managing time, fear of failure, and lack of self-control, while motivation was in the moderate category. External factors identified as high-category were environmental conditions, while parental upbringing was classified as moderate. Based on these results, counselors can offer tailored guidance and counseling services to help students address academic procrastination effectively.